2001
DOI: 10.2166/wst.2001.0725
|View full text |Cite
|
Sign up to set email alerts
|

Comparative survival of enteric viruses and bacteria in Atlantic Ocean seawater

Abstract: The survival of Escherichia coli, Salmonella typhi, Shigella sonnei, poliovirus type 1 and a parvovirus (Minute Virus of Mice) was determined in seawater. Seeded seawater was incubated in the laboratory at 6, 12, 20 and 28 degrees C for up to 40 d. In-situ survival studies were done seasonally (winter, spring, summer and fall) using seeded microbial dialysis equipment placed in the Atlantic Ocean off coastal North Carolina at water depths of 3-10 m. In laboratory studies all test microbes survived longer at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 6 publications
3
53
0
Order By: Relevance
“…In a study comparing in vitro and in situ survival in seawater, viruses survived significantly longer at lower temperatures in laboratory conditions, but despite a similar temperature range in field studies, there was no significant difference in poliovirus survival between seasons in natural water (163). Likewise, Wetz et al (165) showed that virus survival at both 22°C and 30°C in unfiltered natural seawater was much shorter than survival in filtered seawater or artificial seawater at either temperature.…”
Section: Aquatic Environmental Factorsmentioning
confidence: 97%
“…In a study comparing in vitro and in situ survival in seawater, viruses survived significantly longer at lower temperatures in laboratory conditions, but despite a similar temperature range in field studies, there was no significant difference in poliovirus survival between seasons in natural water (163). Likewise, Wetz et al (165) showed that virus survival at both 22°C and 30°C in unfiltered natural seawater was much shorter than survival in filtered seawater or artificial seawater at either temperature.…”
Section: Aquatic Environmental Factorsmentioning
confidence: 97%
“…D values for MS2 phage were significantly greater than D values for FCV and E. coli at 4 and 25°C (Table 1) Previous research has shown that NV can survive for long periods of time in the environment (1,26,38). Thus, a useful indicator of this pathogen must have, among other features, the ability to survive for a long time in the environment.…”
mentioning
confidence: 88%
“…Findings from these studies affirm persistence of allochthonous microflora in the marine environment. Further, different species of bacteria including pathogenic ones (Colwell et al 1981;Xu et al 1982;Huq et al 1984;McCarthy and Khambaty 1994;McCarthy et al 1996;Wait and Sobsey 2000;Darakas 2001;Ramaiah et al 2002a) survive in seawater for one to several weeks. Once introduced into the marine environment, allochthonous pathogens of human health concerns can disperse far and wide to other regions.…”
Section: Introductionmentioning
confidence: 99%